FFT Analysis on Coupling Effect of Axial and Torsional Vibrations in Circular Cross Section Beam of Steam Turbine Generators - Xiang Xu (Institute of Advanced Engineering and Science, 2014)
This paper presents a novel method to nonlinearly investigate the dynamics of the coupled axial and torsional vibrations in the circular cross section beam of the steam turbine generator using the FFT analysis. Firstly, the coupled axial and torsional vibrations of a beam are proved by equivalent law of shearing stress and different boundary conditions. Then, a nonlinear mathematical model of the coupled axial and torsional vibrations is established by the Galerkin method. Lastly, the fast Fourier transform (FFT) is employed to investigate the coupled effect of the beam vibration. A practical calculation example is calculated numerically and the coupled mechanism of the beam’s axial and torsional vibrations is analyzed in detail. The analysis results show that the frequencies of the coupled response would be existed in some special orders and the coupled response frequencies are smaller than the single vibration. Since for the first time the coupled mechanism of the beam’s axial and torsional vibrations is theoretically analyzed, the findings in this work may provide directive reference for practical engineering problems in design of steam turbine generators. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4379